Sheikh Ahmad ibn Zaini Dahlan's Response to the Radical Shia Movement of Qaramithah: A Historical Study of the Book of Tarih Zaini al-Dini Dahlan - Syamsuri Ali (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The purpose of this research is to find out Sheikh Ahmad ibn Zaini Dahlan's Response to the Radical Shia Movement of Qaramithah. This study is qualitative-descriptive to trace the sources of literature (library research) using the History method. The method is carried out with four activity processes: heuristics, criticism, verification and histriography. Based on the results of this study, it is known that the Shiite Qaramithah Movement received a negative response from Sheikh Ahmad ibn Zaini Dahlan, who directly accused him of being a "mulhid" (heretical) movement. His views as written in histriographic works are supported by historical evidence, which shows the Qaramitha Shia movement carried out radicalism in its ideological practices which lead to justification of acts of terrorism against Islamic society and create political chaos against legitimate government.